The effect and safety of constraint-induced movement therapy for post-stroke motor dysfunction: a meta-analysis and trial sequential analysis - Zhang, Jiaming; Xiao, Xianjun; Jin, Qizu; Li, Juan; Zhong, Dongling; Li, Yuxi; Qin, Yan; Zhang, Hong; Liu, Xiaobo; Xue, Chen; Zheng, Zhong; Jin, Rongjiang (Frontiers in Neurology, 2023)
Background Due to motor function insufficiency, patients with post-stroke motor dysfunction (PSMD) have limitations in performing an activity, feel restricted during social participation, and feel impaired in their quality of life. Constraint-induced movement therapy (CIMT) is a neurorehabilitation technique, but its effectiveness on PSMD after stroke still remains controversial. Objective This meta-analysis and trial sequential analysis (TSA) aimed to comprehensively evaluate the effect and safety of CIMT for PSMD. Methods Four electronic databases were searched from their inception to 1 January 2023 to identify randomized controlled trials (RCTs) investigating the effectiveness of CIMT for PSMD. Two reviewers independently extracted the data and assessed the risk of bias and reporting quality. The primary outcome was a motor activity log for the amount of use (MAL-AOU) and the quality of movement (MAL-QOM). RevMan 5.4, Statistical Package for Social Sciences (SPSS) 25.0, and STATA 13.0 software were used for statistical analysis. The certainty of the evidence was appraised using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. We also performed the TSA to assess the reliability of the evidence. Results A total of 44 eligible RCTs were included. Our results showed that CIMT combined with conventional rehabilitation (CR) was superior to CR in improving MAL-AOU and MAL-QOM scores. The results of TSA indicated that the above evidence was reliable. Subgroup analysis demonstrated that CIMT (≥6 h per day or duration ≤ 20 days) combined with CR was more effective than CR. Meanwhile, both CIMT and modified CIMT (mCIMT) combined with CR were more efficient than CR at all stages of stroke. No severe CIMT-related adverse events occurred. Conclusion CIMT may be an optional and safe rehabilitation therapy to improve PSMD. However, due to limited studies, the optimal protocol of CIMT for PSMD was undetermined, and more RCTs are required for further exploration. Clinical trial registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=143490, identifier: CRD42019143490.